The role of social media in promoting sport: Malaysian football / Muhammad Syaril Azlie…[et.al] - Azlie, Muhammad Syaril; Ibrahim, Nur Shakinah; M.Faridul Halim, Nur Azureen; Moamed Tahir, Nurul Hazie Sharmira; Sulaiman, Muhammad Zulkifli; Jaafar, Syamwill (Faculty of Communication and Media Studies, 2016)
This aim of this study seeks to understand how social media is being used amongst sports organizations. More specifically, this study analyses the perspective and the role of social media in Football Association Malaysia. A few research before has established the importance of social media in promoting sports and entertainment venues but hard to elaborate on how individual teams utilize social media strategy, and the current situation around social media in sports communication. To establish best practices of social media in sports communication specific to the Football Association Malaysia (FAM). This research is using qualitative method. This study interviewed social media specialists from FAM, sport journalist, Malaysian football player and academician. It have been proven that social media help in sharing information and making stronger relationship with fans. Besides they should cover all aspect and medium not only social media in order to bring back the reputation. These best result explain the most effective ways to utilize social media in sports communication specific to the FAM. These best solution and result can also be translated and used across other sports teams, brands an entertainment entities.